The beginning and the end: flanking nucleotides induce a parallel G-quadruplex topology - Chen, Jielin; Cheng, Mingpan; Salgado, Gilmar F; Stadlbauer, Petr; Zhang, Xiaobo; Amrane, Samir; Guédin, Aurore; He, Fangni; Šponer, Jiří; Ju, Huangxian; Mergny, Jean-Louis; Zhou, Jun (Nucleic acids research, 2021)
Genomic sequences susceptible to form G-quadruplexes (G4s) are always flanked by other nucleotides, but G4 formation in vitro is generally studied with short synthetic DNA or RNA oligonucleotides, for which bases adjacent to the G4 core are often omitted. Herein, we systematically studied the effects of flanking nucleotides on structural polymorphism of 371 different oligodeoxynucleotides that adopt intramolecular G4 structures. We found out that the addition of nucleotides favors the formation of a parallel fold, defined as the 'flanking effect' in this work. This 'flanking effect' was more pronounced when nucleotides were added at the 5'-end, and depended on loop arrangement. NMR experiments and molecular dynamics simulations revealed that flanking sequences at the 5'-end abolish a strong syn-specific hydrogen bond commonly found in non-parallel conformations, thus favoring a parallel topology. These analyses pave a new way for more accurate prediction of DNA G4 folding in a physiological context.
Keywords: nukleotidy; G-Quadruplexes; DNA; Molecular Dynamics Simulation; konformace nukleové kyseliny; G-kvadruplexy; simulace molekulární dynamiky; Nucleic Acid Conformation; Nucleotides; oligonukleotidy; Oligonucleotides; vodíková vazba; RNA; Hydrogen Bonding; polymorfismus genetický; cirkulární dichroismus; Circular Dichroism; Polymorphism, Genetic